Multicentric hepatic EBV-associated smooth muscle tumors in an AIDS patient: a case report, investigation of mTOR activation and review of the literature - Shen, Qi (e-Century Publishing Corporation, 2011)
Epstein-Barr virus (EBV) - associated smooth muscle tumors (EBV-SMT) are a rare, recently recognized distinct group of mesenchymal tumors that develop exclusively in patients with immunosuppression. It is believed that tumorigenesis is, at least in part, through the activation of the Akt/mammalian target of rapamycin (mTOR) signal pathway. We describe the clinicopathologic and immunohistochemical features of a multifocal hepatic EBV-SMT in a 34-year-old acquired immunodeficiency syndrome (AIDS) patient and investigate the activation status of the mTOR signal pathway in this tumor. In addition, we provide a review of the literature on the clinicopathologic findings of hepatic EBV-SMT in adult AIDS patients, and discuss their biologies and possible therapeutic strategies.